2017
DOI: 10.1177/0300060516668939
|View full text |Cite
|
Sign up to set email alerts
|

Association of VDR polymorphisms (Taq I and Bsm I) with prostate cancer: a new meta-analysis

Abstract: ObjectiveProstate cancer is a malignant tumour that poses a serious risk to human health. Epidemiological studies suggest that it may be associated with vitamin D receptor gene (VDR) polymorphisms. Previous work investigated potential risks between Taq I (rs731236) and Bsm I (rs1544410) VDR polymorphisms with prostate cancer in humans; however, results are inconsistent.MethodsWe conducted a meta-analysis to retrieve genetic association analyses of rs731236 and rs1544410 polymorphisms with prostate cancer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…In the case of cancer, polymorphisms of the vitamin D receptor (VDR) have been linked to the onset of prostate cancer (Liu et al . ). The fact that the ability of the skin to make vitamin D declines as ageing progresses is one reason why cognition tends to decline during ageing (MacLaughlin & Holick, ; Kennel et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the case of cancer, polymorphisms of the vitamin D receptor (VDR) have been linked to the onset of prostate cancer (Liu et al . ). The fact that the ability of the skin to make vitamin D declines as ageing progresses is one reason why cognition tends to decline during ageing (MacLaughlin & Holick, ; Kennel et al .…”
Section: Introductionmentioning
confidence: 97%
“…A previous publication has reported that the Taq I (rs731236) polymorphism affects VDR transcriptional activity and mRNA stability, thus altering the abundance of VDR protein, and in turn affecting vitamin D levels (39). Liu S. and colleagues (40) have conducted a meta-analysis to retrieve genetic association analyses of rs731236 and rs1544410 polymorphisms with PCa from studies published between 2006 and 2016. Their findings suggest a significant association between rs731236 and PCa risk in Asians and African Americans, but rs1544410 was not associated with PCa under three genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results have been disputable [ 20 22 ]. Previous meta-analyses were reported by Yin et al in 2009, Fei et al in 2016 and Liu et al in 2017 [ 10 , 23 , 24 ], in which the number of included studies was 23, 27 and 8, respectively. However, some new data was reported, which is not consistent with the results of the former three studies [ 17 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taq I polymorphism (rs731236) is one of the most widely-studied SNPs. It is a synonymous mutation located in exon 9 of VDR gene [ 10 ]. This mutation could reduce the mRNA stability and therefore decrease the mRNA levels of VDR gene [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation